1996
DOI: 10.1002/art.1780390623
|View full text |Cite
|
Sign up to set email alerts
|

Depressive symptoms associated with scleroderma

Abstract: Objective. To examine the prevalence and correlates of depressive symptoms among patients with systemic sclerosis (SSc; scleroderma).Method. Fifty-four outpatients with scleroderma were administered the Beck Depression Inventory, the Neuroticism-Extraversion-Openness Personality Inventory, the Health Assessment Questionnaire, and the Psychosocial Adjustment to Illness Scale. In addition, patients underwent a comprehensive clinical assessment, and pulmonary function tests were obtained.Results. Nearly half of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
86
1
11

Year Published

1999
1999
2016
2016

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 95 publications
(115 citation statements)
references
References 21 publications
17
86
1
11
Order By: Relevance
“…As far as the scleroderma patients are concerned, the literature is considerably poor regarding the kind and the degree of their psychiatric symptomatology. Only one study deals with the core of the problem: the prevalence of psychiatric symptomatology in patients with scleroderma [8]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As far as the scleroderma patients are concerned, the literature is considerably poor regarding the kind and the degree of their psychiatric symptomatology. Only one study deals with the core of the problem: the prevalence of psychiatric symptomatology in patients with scleroderma [8]. …”
Section: Discussionmentioning
confidence: 99%
“…In another study [7]a psychosocial investigation of sclerodermatic patients was carried out. Only one published study on the prevalence of psychiatric symptomatology, namely depression [8], in patients with scleroderma can be found in the literature. In this study, almost half of the patients with scleroderma presented mild depressive symptoms and an additional 17% of moderate to severe levels.…”
Section: Introductionmentioning
confidence: 99%
“…It affects mainly women in the prime of their life (3,4) and is associated with significant morbidity (including disability and depression) (5,6), increased mortality (relative survival as low as 35% at 20 years, compared with age-, sex-, and race-matched individuals) (7), and high costs (8). SSc is thought to affect more than 16,000 Canadians and up to 100,000 Americans (9 -13).…”
Section: Introductionmentioning
confidence: 99%
“…10 Increased vasospasm has been demonstrated in the main internal organs (heart, kidney, and lung) in scleroderma 11 and might explain why some middle-aged scleroderma patients have otherwise unexplained transient ischemic attacks with focal neurological defects 3,14,15 or transient global amnesia, 16 both of which were observed in our patients. In addition, various psychological disorders have been reported in scleroderma patients 15,[17][18][19] and may be partly due to organic brain involvement; indeed, it has recently been shown that patients with basal ganglia calcification frequently have neuropsychological alterations. 20 We believe that the use of sensitive tools for assessing CNS involvement should be included in a comprehensive assessment of the neuropsychological disorders observed in systemic sclerosis.…”
Section: Discussionmentioning
confidence: 99%